The effect of dietary calcium source, concentration and particle size on calcium retention, eggshell quality and overall calcium requirement in laying hens - Lichovnikova, M (British poultry science, 2007)
1. Four different sources of calcium in isonitrogenous and isoenergeric diets were fed to laying hens for 2 weeks when they were 56 and 57 weeks old. The calcium source blends were as follows: 29% fine limestone (LF)+71% large limestone (LG), 32% LF+68% eggshell, 32% LF+68% oyster shell, 50% LF+50% LG. The contents of these blends of calcium in the diets were as follows: 103.3, 93.3, 93.3 and 93.3 g/kg, respectively. 2. The coefficients of calcium retention were significantly higher in 50:50 LF:LG (0.578) and 32:68 LF:eggshell (0.576). The midnight feeding significantly improved the coefficient of calcium retention in all mixtures except 50:50 LF:LG. 3. In the mixtures 29:71 LF:LG and 32:68 LF:oyster shell, there were significantly greater eggshell quality, eggshell weight, eggshell thickness and eggshell strength. Midnight feeding had no significant effect on eggshell quality. 4. In the ration with oyster shells, 96.5% of the retained calcium was deposited in the eggshell, but in rations 32:68 LF:eggshell and 50:50 LF:LG the utilisation was only 73.9 and 78.6%, respectively. 5. To ensure good quality eggshells in the last third of production, the recommendation for calcium is 4.1 g/kg (900 g/kg dry matter, feed intake 110 g/d). As a source of calcium in this stage of production, a feed mixture containing two-thirds large particles should be used (limestone grit or oyster shell).
Keywords: Calcium; vápník; Egg Shell; Female; Animal Feed; kur domácí; Animals; ženské pohlaví; vaječná skořápka; velikost částic; krmivo pro zvířata; Particle Size; Calcium, Dietary; zvířata; Chickens; vápník dietní